Dating terrestrial impact structures: U‐Pb depth profiles and (U‐Th)/He ages of zircon. Issue 12 (25th June 2014) - Wielicki, Matthew M.; Harrison, T. Mark; Stockli, Daniel
Abstract We investigate the presence of epitaxial overgrowth rims and "reset" zircon, complete loss of radiogenic lead (Pb*), from terrestrial impactites to constrain the occurrence of such phenomenon in impact environments and their possible use in dating impact events. We also explore (U‐Th)/He dating of zircon to evaluate this geochronometer in accurately identifying impact ages, particularly when no dateable melt sheet exists. Our results show that (U‐Th)/He ages of zircon from the brecciated, and presumably shocked target, can accurately date an impact event and provides another tool to determine impact ages when no melt sheet exists, an alternative to problematic interpretations of commonly used apparent 40Ar/39Ar plateau ages. No evidence of epitaxial overgrowth rims and/or reset zircon was observed, suggesting that zircons within shocked impactites have remarkably slow Pb diffusion and possibly explaining the relatively few reset grains reported in terrestrial impactites.